Sustainable wastewater treatment plants design through multiobjective optimization - Padrón-Páez, Juan I.; Almaraz, Sofía De-León; Román-Martínez, Alicia (Computers & chemical engineering, 2020)
•An integrated framework that combines conceptual and mathematical programming approaches, for the design of sustainable WWTPs has been proposed with the required methodology and computer-aided tools.•The framework was applied to a case study for the treatment of municipal wastewater from mexico City, where many different potential WWTP configurations were assessed using optimization approaches considering a multiobjective function which includes the three dimensions of sustainability (economic, environmental and social).•The best trade-off WWTP design, that maximizes the wastewater reuse while minimizes the total cost and the energy consumption in a compromised solution, is obtaining by using a hybrid multiobjective optimization technique (lexicographic + ε-constraint) and a multiple criteria decision-making method (M-TOPSIS). Nowadays, an adequate design of wastewater treatment plants taking into consideration all sustainability dimensions– economic, environmental and social- is fundamental. This can be achieved by implementing systematic methodologies where conceptual and mathematical tools can be used together. This contribution proposes a framework that uses total cost, consumed energy, and reclaimed wastewater as sustainability metrics. A mixed-integer nonlinear programming problem arises from a general superstructure for wastewater treatment plants. A case study from Mexico City is solved by a hybrid multiobjective optimization approach that combines lexicographic and ε-constraint methods. Solutions are provided in the form of a Pareto front. A modified technique for order of preference by similarity to ideal solution (M-TOPSIS) analysis is used as a multiple criteria decision-making tool to find the best trade-off solution. The optimal sustainable configuration resulted consists of three levels of treatment and 100% of treated water reuse. [Display omitted]